Lipid-independent control of endothelial and neuronal TRPC3 channels by light - Tiapko, Oleksandra; Freichel, Marc (Chemical science, 2019)
Lipid-gated TRPC channels are highly expressed in cardiovascular and neuronal tissues. Exerting precise pharmacological control over their activity in native cells is expected to serve as a basis for the development of novel therapies. Here we report on a new photopharmacological tool that enables manipulation of TRPC3 channels by light, in a manner independent of lipid metabolism and with higher temporal precision than lipid photopharmacology. Using the azobenzene photoswitch moiety, we modified GSK1702934A to generate light-controlled TRPC agonists. We obtained one light-sensitive molecule (OptoBI-1) that allows us to exert efficient, light-mediated control over TRPC3 activity and the associated cellular Ca2+ signaling. OptoBI-1 enabled high-precision, temporal control of TRPC3-linked cell functions such as neuronal firing and endothelial Ca2+ transients. With these findings, we introduce a novel photopharmacological strategy to control native TRPC conductances.
Gesehen am 27.03.2019